2009
DOI: 10.3201/eid1508.081511
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussisStrains with Increased Toxin Production Associated with Pertussis Resurgence

Abstract: A more virulent strain of the disease is emerging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
338
1
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(368 citation statements)
references
References 36 publications
14
338
1
15
Order By: Relevance
“…Although the ptxP3 allele is thought to increase pertussis toxin expression (40,41), a recent comparison of isogenic mutants found that the ptxP3 allele and the genetic background, which includes genomic structure, independently enhance colonization in mice (42). Similarly, although alleles of fimH contain polymorphisms in the predicted surface epitope region, differences in immune recognition remain untested (43).…”
Section: Discussionmentioning
confidence: 99%
“…Although the ptxP3 allele is thought to increase pertussis toxin expression (40,41), a recent comparison of isogenic mutants found that the ptxP3 allele and the genetic background, which includes genomic structure, independently enhance colonization in mice (42). Similarly, although alleles of fimH contain polymorphisms in the predicted surface epitope region, differences in immune recognition remain untested (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to conventional resistance mechanisms (e.g., efflux pumps to thwart drugs or antigenic variation to escape vaccine‐induced immunity), experiments have shown that parasite virulence can evolve in response to—and mitigate the effects of—medical interventions, as exemplified by Marek's disease virus in response to vaccines (Read et al., 2015), and rodent malaria parasites in response to drugs (Schneider et al., 2012) and vaccines (Barclay et al., 2012). The extent of this kind of evolution in nonexperimental systems is poorly understood, but there is some evidence of vaccine‐driven virulence evolution in parasites of humans (pertussis, Mooi et al., 2009), cats (feline calicivirus, Radford, Dawson, Coyne, Porter, & Gaskell, 2006) and poultry (Marek's disease virus, Nair, 2005; avian infectious bursal disease virus, van den Berg, 2000). Through the development of general theory, Gandon, Mackinnon, Nee, and Read (2001) formalized the prediction that imperfectly effective, or “leaky” vaccines can drive virulence evolution.…”
Section: Introductionmentioning
confidence: 99%
“…For ptxP sequence-based typing, the promoter region was amplified using primers and conditions based on those previously described (Mooi et al, 2009;and M. van Gent, personal communication). Each 20 ml PCR contained 10 ml HotStarTaq Master Mix (Qiagen), 1 mM each primer, 1 M betaine (Sigma) and 2 ml DNA extract (for both bacterial isolates and clinical samples).…”
Section: Methodsmentioning
confidence: 99%
“…Characterizing changes in genes encoding known vaccine antigens or virulence factors such as the S1 and S3 subunits of pertussis toxin (ptxA and ptxC), pertactin (prn), tracheal colonization factor (tcfA) and fimbrial antigens 2 and 3 (fim2 and fim3) is also valuable (Mooi et al, 2007;Packard et al, 2004;Tsang et al, 2004;van Loo et al, 2002). Polymorphisms in the pertussis toxin promoter (ptxP) have also been proposed to affect the virulence of B. pertussis through increased Ptx production (Mooi et al, 2009;Mooi, 2010), although an increase in virulence was not seen in a recent study using a murine model of infection (Hegerle et al, 2012). Other methods designed to distinguish isolates, which are not linked to virulence factors, include PFGE, multilocus variablenumber tandem repeat analysis (MLVA) and genome-wide single nucleotide polymorphism (SNP) analysis (Mooi et al, 2000;Octavia et al, 2011;Schouls et al, 2004;van Gent et al, 2011).…”
Section: Introductionmentioning
confidence: 99%